Estudos culturais, educação e pedagogia - Marisa Costa Vorraber; Rosa Silveira Hessel; Luis Henrique Sommer (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2003)
Presents a panoramic view of the emergence, the constitution and the development of Cultural Studies as a multifaceted area which conceives culture as a battlefield and political arena. The connections and clashes with Marxisms, feminisms and their opposition to racism are highlighted, as well as their approximation and crossings with theoretical issues and methodological tendencies. A sketch is made of their development in Latin America, with special emphasis on those themes and dimensions which are most frequently tackled and debated. In this case, the deep immersion in cultural issues of the continent, such as the local-global tension, the hybridisation of identities, the audiences, within an increasing thematic multiplicity are emphasised. Starting from this panorama, the close relations between Cultural Studies, education and pedagogy are discussed, presenting as an example a short review of the plurality of works already carried out in this new area in Brazil, as well as through a specific reflection on the linkage between Cultural Studies and the school.